Total glycosides and polysaccharides of Cistanche deserticola prevent osteoporosis by activating Wnt/β-catenin signaling pathway in SAMP6 mice. (10th May 2021) - Wang, Fujiang; Tu, Pengfei; Zeng, Kewu; Jiang, Yong
Abstract: Ethnopharmacological relevance: Traditional Chinese medicine Cistanche deserticola Y. C. Ma has effect of "tonifying kidney and strengthening bone". However, the specific active extracts of C. deserticola and mechanisms for treatment of osteoporotic are not clear. Aim of the study: We wanted to identify the effective component extracts of C. deserticola for the treatment of osteoporosis and the potential mechanisms. Materials and methods: Our group researched the extracts of C. deserticola with anti-osteoporotic activity, including total glycosides (TGs), polysaccharides (PSs), and oligosaccharides (OSs) in senescence accelerated mouse prone 6 (SAMP6) mice. The Goldner's Trichrome, Van Gieson's (VG), Safranin O-Fast Green staining and Von Kossa staining were performed to investigate the bone structure formation and calcium deposits. Serum was collected for detecting biochemical markers. Bone micro-architecture was detected by micro-CT. Expressions of bone morphogenetic protein-2 (BMP-2), osteocalcin (OCN), osteoprotegerin (OPG), receptor activator of nuclear factor-κ B ligand (RANKL), p-glycogen synthetase kinase-3β (p-GSK-3β), and p-β-catenin were analyzed by western blotting and immunohistochemistry. Results: TGs and PSs ameliorated bone histopathological damages, promoted the formation of new bone, collagenous fiber, and chondrocytes, and accelerated the calcium deposits. Moreover, they remarkable altered the biomarkers of bone turnover and effectively ameliorated bone microarchitecture. The further mechanisms study showed that TGs and PSs significantly decreased the expressions of RANKL, p-β-catenin, as well as up-regulated the expression of BMP-2, OCN, OPG, and p-GSK-3β (Ser9). Conclusion: The findings of this study suggest that TGs and PSs can promote osteoblastogenic bone formation and improve bone microstructure damage in SAMP6 mice, and their therapeutic effect on osteoporosis is via activating Wnt/β-catenin signaling pathway. Graphical abstract: Image 1